SKRINING FITOKIMIA EKSTRAK JAMUR KANCING (Agaricus bisporus) - Asriani Suhaenah; Siska Nuryanti (Jurnal Fitofarmaka Indonesia, 2017)
The phytochemical screenings and analysis of chemical compounds in n-hexan extract, ethyl acetat extract and ethanol extract, of Agaricus bisporus with Thin Layer Chromatography (TLC) has been carried out. Extraction process was performed with terraced maceration, identification of bioactive compound with thin layer chromatography. The result of Thin Layer Chromatography test showed that n-hexane extract contains flavonoid, coumarin, therpenoid and steroid. Ethyl acetate extract contains flavonoid, coumarine, therpenoid. Ethanol extract contains flavonoid, alkaloid, polyphenol, coumarin, terpenoid.